(untitled) (Experimental biology, 2017)
The article presents the geobotanical characteristic and analysis of plant com- munities flora’s with the rare and endemic plant species of Kazakhstan flora Lonicera iliensis Pojark., found in the middle flow of the Ili River, below the Kapchagai hy- dropower plant, near the village of Bakanas in Balkhash district of Almaty region. Within population 105 plant species belonging to 90 genera and 34 families were registered. The leading families are Asteraceae, Chenopodoaceae, Brassicaceae, Fa- baceae and Poaceae. To the share of these five families are belong 52 species (50%) of plant communities flora. Our observations have shown that the vital state of Lonicera iliensis is satisfac- tory. Within this population occur young generative, adults generative and senile individuals. However, recovery of Lonicera iliensis population is very slow. The causes are different. The main of them –moisture deficit, overgrazingand a high probability of fires caused by the fault of tourists and fishermens. Considering of this, the authors recommend to protect the areas of Lonicera iliensis populations which located in middle and lower reaches of the river Ili and to introduce it in the botani- cal gardens of the Republic of Kazakhstan.